Common mental disorders in mothers of children attending out-patient malnutrition clinics in rural North-western Nigeria: a cross-sectional study - Aminu T. Abdullahi; Zubaida L. Farouk; Abdulazeez Imam (BMC, 2021)
Abstract Background Children with uncomplicated severe acute malnutrition are managed routinely within out-patient malnutrition treatment programs. These programs do not offer maternal mental health support services, despite maternal mental health playing a significant role in the nutritional status of children. Additionally, the burden of maternal Common Mental Disorders (CMDs) is poorly described among mothers of children attending these programs. This study thus determined the burden and risk factors for maternal CMDs among children attending out-patient malnutrition clinics in rural North-western Nigeria. Methods We conducted a cross-sectional study among 204 mothers of children with severe acute malnutrition who attending eight out-patient malnutrition clinics in Jigawa, North-western Nigeria. We used the World Health Organization Self-Reporting Questionnaire-20 (WHO SRQ-20) screening tool, a recognised and validated proxy measure for CMDs to identify mothers with CMDs. The prevalence of maternal CMDs was determined by identifying the proportion of mothers with SRQ scores of ≥8. Risk factors for CMD were determined using multivariable logistic regression. Results Maternal CMD prevalence in children attending these facilities was high at 40.7%. Non-receipt of oral polio vaccine (OPV) (AOR 6.23, 95%CI 1.85 to 20.92) increased the odds for CMD. While spousal age above 40 (AOR 0.95, 95%CI 0.90 to 0.99) and long years spent married (AOR 0.92, 95%CI 0.85 to 0.98) decreased the odds for CMD. Conclusions Our findings indicate maternal CMD burden is high in out-patient malnutrition clinics in North-western Nigeria. Maternal mental health services would need to be integrated into the community management of acute malnutrition programs to provide more holistic care, and possibly improve long-term outcomes after discharge from these programs.